2023
DOI: 10.1093/ejendo/lvad038
|View full text |Cite
|
Sign up to set email alerts
|

Mild autonomous cortisol secretion in adrenal incidentalomas and risk of fragility fractures: a large cross-sectional study

Abstract: Objective Mild autonomous cortisol secretion (MACS) has been associated with a higher prevalence of osteoporosis, although most data rely on single-center studies with limited sample size. We aimed to assess the prevalence of fragility fractures and contributing factors in a large cohort of patients with adrenal incidentalomas. Design and Methods Medical records of 1023 patients with adrenal incidentalomas from 1990 to 2019 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
2
13
2
Order By: Relevance
“…Previous studies in patients with adrenal tumors have found increased fracture risk in individuals with higher cortisol levels . In contrast to the current study, these studies did not exclude individuals with MACS.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…Previous studies in patients with adrenal tumors have found increased fracture risk in individuals with higher cortisol levels . In contrast to the current study, these studies did not exclude individuals with MACS.…”
Section: Discussioncontrasting
confidence: 76%
“…However, Li et al had medical records available since 1966 in their examined county, whereas we had only national data using ICD-10 , which was introduced in Sweden in 1997 (ie, an almost 20-year difference, which may explain the prevalence difference). Moreover, our vertebral fracture prevalence rate of 1.5% in patients with NFATs (compared with 0.9% in controls) was also much lower than the 6.4% reported by Li et al but even lower compared with the rates of 22.9% to 24.7% reported by other recent studies . We suspect that this drastic difference in prevalence is due to inclusion of asymptomatic vertebral fractures in the previous studies because all patients with NFATs had their spines evaluated radiologically, whereas our study and the study by Li et al possibly included only symptomatic vertebral fractures.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Testing for Cushing syndrome can be considered in select patients with clinical features strongly associated with Cushing syndrome (Table 1), such as osteoporosis and vertebral fractures, among those younger than 50 years and those with incidentally identified asymptomatic adrenal tumors …”
Section: Diagnosis Of Cushing Syndromementioning
confidence: 99%